The Impact Of Iklanku Shopee Feature Through Brand Awareness On Purchase Decisions Using SEMPLS, Naive Bayes and K-NN Method - Dharma, Ni Putu Intan Waindika; Putra, I Ketut Gede Darma; Mandenni, Ni Made Ika Marini; Yasin, Yusliza Binti Mohd (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 10 No 1 (2022): Vol. 10, No. 1, April 2022DO - 10.24843/JIM.2022.v10.i01.p07, 2022)
The purpose of this study was to examine the effect of my Shopee Advertising Feature on Purchase Decisions and Brand Awareness. Testing the effect of Brand Awareness on Purchase Decisions and analyzing the role of Brand Awareness in mediating the effect of my Ads feature on Purchase Decisions. This research is motivated by the phenomenon of inequality that occurs in economic conditions that are weakening due to COVID-19 but the purchase of fashion products has actually increased. Data obtained from the distribution of questionnaires is as much as 350 data. SmartPLS is used to find the outer model and inner model. The results of the data are reprocessed to determine clusters and classification using K-Means, Naive Bayes and K-NN in the RapidMiner application. The results obtained from this research are that my Advertisement Shopee feature has a positive and significant effect on Purchase Decisions and Brand Awareness. Brand awareness has a positive and significant effect on Purchase Decisions and Brand Awareness also mediates positively and significantly the influence of the My Shopee Advertising feature on Purchase Decisions. The results obtained from data mining processing are that the Naive Bayes algorithm is more accurate than the K-NN algorithm method in classification using split data and also cross validation. Keywords: Brand Awareness, Iklanku Shopee Feature, K-NN, Naive Bayes, Purchase Decision